The forecast for poverty: A review of the evidence - Skoufias, Emmanuel (2012)
Fil: Rabassa, Mariano Javier. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina